The life cycle of Eucheilota medusifera ? (Torrey, 1902), comb. nov. [=Campalecium medusiferum] (Cnidaria: Hydrozoa: Lovenellidae) from the Bay of Biscay (northeastern Atlantic), including a description of the adult medusa - Altuna, Álvaro (Zootaxa, 2008)
The life cycle of Campalecium medusiferum ? Torrey, 1902 (Cnidaria: Hydrozoa) was traced in the laboratory from material collected from the Bay of Biscay (northeastern Atlantic). Both newly released and one-month-old male medusae with fully-grown gonads are described, with remarks on their biology and behaviour. The adult medusa corresponds with the diagnosis of Eucheilota McCrady, 1859, and the species is reassigned from Haleciidae Hincks, 1868 to Lovenellidae Russell, 1953. The genus Campalecium Torrey, 1902 can be considered valid only if the characters of a species with Halecium-like polyps and Eucheilota-like medusae are considered of generic significance. Instead, the species studied here is assigned to Eucheilota, as E. medusifera ? (Torrey, 1902) (comb. nov.), and Campalecium is considered a likely synonym of that genus. The medusa is different from Lovenella cirrata (Haeckel, 1879), type species of the genus Mitrocomium Haeckel, 1879, previously suggested to have been linked to the same hydroid in the Mediterranean. A supposed connection between medusae of L. cirrata and Halecium-like hydroids cannot be supported, and assigning these hydroids to Mitrocomium is rejected. Future studies may prove that Halecium-like hydroids release medusae of diverse genera within the family Lovenellidae.